Computer-aided design (CAD) of DC machine using MATLAB / Mohd Suhaidi Wahib - Wahib, Mohd Suhaidi (2006)
In recent years, product life cycle has decreased and demands for new products have emerged due to competition, modern industrial needs, and rapidly changing technology. This has necessitated changes in design, development, and manufacturing processes to improve quality and efficiency and to reduce cost. Computer-aided design (CAD) helps to meet this challenge in the design evaluation and final product design stages. This paper presents the development of interactive software for the optimal design of dc machine using Matlab. These will give the idea to the industry for manufacturing the electric machine especially dc machine easily.